O município de Ribeirão das Neves: um 'bairro popular' em um centro metropolitano - Paola Rogedo Campos (2009)
This work analyses the sociospatial segregation process in the metropolis of Belo Horizonte formation, looking at the housing production for low income classes. Looking for a better understand about sociospatial segregation, the analysis has for reference the Municipality of Ribeirão das Neves, an example of a peripheral space, most of all occupied by a poor and metropolitan center excluded population, and off controlled by State government, since its formation. The municipality has a dual insertion in a metropolitan context: a popular borough in a penitentiary space. Thus, the wanting Ribeirão das Neves population manage the housing problem especially by autoconstruction. The work aims to think about the housing industrial construction acting in the cities formation process and its difficulty to meet the needs of low income classes, that have been clearly pointed out in studies on the brasilian housing déficit. Therefore, significantly the government mediationin the housing market is required, especially to create sources of subsidy and financing housing units for low income classes and directives to integrate housing policy with urban policy.